2020
DOI: 10.1007/s10236-020-01428-7
|View full text |Cite
|
Sign up to set email alerts
|

Global tide simulations with ICON-O: testing the model performance on highly irregular meshes

Abstract: The global tide is simulated with the global ocean general circulation model ICON-O using a newly developed tidal module, which computes the full tidal potential. The simulated coastal M2 amplitudes, derived by a discrete Fourier transformation of the output sea level time series, are compared with the according values derived from satellite altimetry (TPXO-8 atlas). The experiments are repeated with four uniform and sixteen irregular triangular grids. The results show that the quality of the coastal tide simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 44 publications
2
39
0
Order By: Relevance
“…Ongoing development work will further explore ICON-specific opportunities like grid refinement in ICON-O (Logemann et al, 2021) and nesting in the atmosphere (Jungandreas et al, 2021). The excellent scaling capabilities of ICON have been documented in the DYAMOND project with ICON-A setups between 80 and 2.5 km (Hohenegger et al, 2020;Stevens et al, 2019) and are further explored in very high resolution coupled set-ups with grid spacing of a few kilometers in the DYAMOND-WINTER project (https://www.esiwace.eu/services/ dyamond/winter).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing development work will further explore ICON-specific opportunities like grid refinement in ICON-O (Logemann et al, 2021) and nesting in the atmosphere (Jungandreas et al, 2021). The excellent scaling capabilities of ICON have been documented in the DYAMOND project with ICON-A setups between 80 and 2.5 km (Hohenegger et al, 2020;Stevens et al, 2019) and are further explored in very high resolution coupled set-ups with grid spacing of a few kilometers in the DYAMOND-WINTER project (https://www.esiwace.eu/services/ dyamond/winter).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on typical climate change experiments, that is, at least century‐long simulations with parameterized physics, the set‐up described here offers an efficient configuration for simulations of past, present and future climates, and large ensembles. It also forms the basis for higher‐resolution versions as well as for configurations using specific properties of the ICON system, for example, grid refinement in ICON‐O (Logemann et al., 2021) or nesting in ICON‐A (Klocke et al., 2017). In this manuscript, we present the first results of ICON‐ESM and provide an examination of the model characteristics in a set of experiments following the CMIP6 Diagnosis, Evaluation, and Characterization of Klima (DECK) protocol and include an ensemble of five CMIP6 “historical” simulations (Eyring et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The basis of our development is the global ocean‐sea ice‐biogeochemistry model ICON‐O (Korn, 2017; Korn & Linardakis, 2018; Logemann et al., 2021). The physical core of the model is based on finite volume numerics.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of adding parameterisation schemes to OGCMs, another way to consider the tidal effect is to add an explicit tidal forcing to the momentum equations. Global tides have been added to some OGCMs (e.g., Thomas et al, 2001;Shriver et al, 2012;Arbic et al, 2018;Logemann et al, 2021), but little research has been conducted from a climatic point of view. By comparing sensitivity runs with and without tidal motions in an OGCM, Schiller (2004) found that tidal motions can rectify Indonesian Archipelago hydrography and the Indonesian Throughflow (ITF) transport.…”
Section: Introductionmentioning
confidence: 99%